Measurement of the False Positive Rate in a Screening Program for Human Immunodeficiency Virus Infections - Burke, Donald S; Brundage, John F; Redfield, Robert R; Damato, James J; Schable, Charles A; Putman, Pamela; Visintine, Robert; Kim, Howard I (The New England journal of medicine, 1988)
In a program screening civilian applicants for U.S. military service for human immunodeficiency virus (HIV) infection, we studied the frequency of false positive diagnoses retrospectively among applicants seropositive for HIV in a subpopulation with a very low prevalence of infection. That subpopulation was defined as consisting of all applicants tested between October 16, 1985, and June 30, 1987, who were young (17 or 18 years of age) and resided in a rural county in a state with a low incidence of reported acquired immunodeficiency syndrome (n = 135,187). Serum specimens from 15 applicants positive for HIV in this low-prevalence subpopulation were retrieved from a serum bank and retested by two Western blot methods, radioimmunoprecipitation, and an immunoassay constructed from a molecularly cloned and expressed viral envelope polypeptide. Fourteen of the 15 samples were unequivocally positive on all retest assays, and 1 was negative. Thus, the measured rate of false positive diagnoses in this program was 1 in 135,187 persons tested. Factors important in achieving a low false positive rate were a redundant, multistep testing algorithm, conservative criteria for interpreting Western blots, the requirement that a second, newly drawn serum specimen be tested for verification before a diagnosis of HIV was considered established, and tight quality control of laboratory testing procedures. We conclude that a screening program for HIV infection in a low-prevalence population can have an acceptably low false positive rate. (N Engl J Med 1988; 319: 961–4.) OVER 1 million persons in the United States are infected with the human immunodeficiency virus (HIV). 1 Routine testing for HIV, with counseling of those who test positive, has been advocated as an effective public health response to the epidemic. 2 There is general agreement that testing may be appropriate for groups thought to be at high risk for infection, such as homosexual men, intravenous drug abusers, and patients of venereal-disease clinics. 3 However, concern has been expressed about the value of routine HIV testing among groups thought to be at lower risk, such as persons applying for marriage licenses, pregnant women, immigrants, . . .